Knowledge, Attitudes, and HIV/AIDS Preventive Behaviors Among Tattooed Papuan Adolescents in Eastern Indonesia: A Cross-Sectional Study of Cultural Risk Factors - Kambu, Yowel (Universitas Nahdlatul Ulama Surabaya, 2025)
HIV/AIDS remains a significant global health challenge, with a 2.3% prevalence in Papua and an estimated 12,050 cases in West Papua by 2024. The prevalent practice of tattooing among Papuan adolescents potentially increases the risk of HIV transmission. This study aimed to analyze the levels of knowledge, attitudes, and preventive behaviours regarding HIV/AIDS among tattooed Papuan ethnic secondary school students in Sorong City. A cross-sectional study was conducted in March 2024 at a secondary school in Sorong City. The sample comprised 150 Papuan ethnic students in Years XI-XII, aged 15-18 years, with tattoo history, selected through purposive sampling. Data were collected using validated questionnaires (Cronbach's alpha >0.7) measuring knowledge (10 items), attitudes (12 items), and preventive behaviours (8 items). Analyses employed descriptive statistics and chi-square tests using SPSS version 25.0. The study received ethical approval (approval number DM.03.05/8/138/2024, dated 17 January 2024). Many respondents (53.3%) demonstrated moderate knowledge levels, 43.3% exhibited neutral attitudes, and 46.7% showed adequate preventive behaviours. Significant positive correlations were found between knowledge and attitudes (r=0.65; p<0.01) and preventive behaviours (r=0.72; p<0.01). Sociodemographic analysis revealed a predominance of respondents aged 17-18 years (46.7%) from middle-income backgrounds. The findings indicate the necessity for culturally sensitive educational interventions to enhance knowledge and promote positive attitudes towards HIV/AIDS prevention among tattooed Papuan ethnic adolescents.